2007
DOI: 10.1007/s12098-007-0151-6
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom poisoning

Abstract: Early diagnosis and treatment in mushroom poisoning can be life saving. Public awareness is very important in prevention of intoxication as well as encouraging early admission to hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 11 publications
0
24
0
2
Order By: Relevance
“…Mushroom poisoning, termed mycetism or mycetismus, most commonly ensues after mushrooms are foraged, misidentified and then consumed [1,7,[9][10][11][12][13][14][15][16][17][18][19][20]. The incidence of ingesting wild, toxic mushrooms is increasingly reported [8,21,22].…”
Section: Overview Of Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Mushroom poisoning, termed mycetism or mycetismus, most commonly ensues after mushrooms are foraged, misidentified and then consumed [1,7,[9][10][11][12][13][14][15][16][17][18][19][20]. The incidence of ingesting wild, toxic mushrooms is increasingly reported [8,21,22].…”
Section: Overview Of Exposurementioning
confidence: 99%
“…Worldwide, hundreds of mushroom poisonings are fatal each year [6,8,23,24]. Most fatalities are secondary to Amanita phalloides ingestions [8,9,12,23].…”
Section: Overview Of Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Çalışmamızda da 20 yaş üstü hastaların oranı % 83 bulunmuştur. Yapılan araştırmalarda da, çalışmamızı destekler şekilde, mantar zehirlenmelerinde kadın olguların yüksek oranda olduğu rapor edilmiştir(12, [16][17][18][19]. Araştırmamızda kadın hastaların mantar zehirlenmelerinin büyük bir oranını oluşturduğu bulundu.…”
Section: Introductionunclassified
“…The review of therapeutic procedures reported on patients intoxicated with amatoxincontaining mushrooms demonstrates a wide variability in medical treatment and overall response rate (Enjalbert et al, 2002;Erguven et al, 2007;Ganzert et al, 2008;Giannini et al, 2007;Kotwica and Czerczak, 2007;Krenova et al, 2007). Thus, evaluation of different therapies of intoxications caused by amatoxin-producing mushrooms seems to be extremely difficult.…”
Section: Introductionmentioning
confidence: 99%